PENGARUH MODEL PROBLEM BASED LEARNING BERBASIS FLIPPED CLASSROOM TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPAS KELAS V UPT SPF SD INPRES BTN IKIP I KOTA MAKASSAR - Nadia Intan Lestari; Muhammad Irfan; Abdul Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study departs from the problem of low critical thinking skills of students in the subject of science and natural sciences. This study uses quantitative research with the type of experimental research that aims to determine the description of the implementation of the problem based learning model based on Flipped Classroom, to determine the description of students' critical thinking skills, and to determine the effect of the problem based learning model based on Flipped Classroom on students' critical thinking skills in the subject of science and natural sciences class V UPT SPF SD Inpres Btn Ikip I. The data collected were then analyzed using descriptive statistical analysis and hypothesis test analysis using the Paired Sample t-test test of the problem based learning model based on Flipped Classroom on the teacher's observation sheet experienced an increase from the first meeting of 88% to the second meeting of 98% with a very good category, and on the student's observation sheet also experienced an increase from the first meeting of 82% to the second meeting of 95% with a very good category. And the results of critical thinking of experimental class students have an average of 85.50 which is included in the very critical category. While the results of the critical thinking test of the control class showed an average of 74.77 which is included in the critical category. Based on the results of inferential statistics, it shows that r count is greater than r table at a significance level of 5%. Thus, H1 is accepted and H0 is rejected. From these results, it can be concluded that there is a positive and significant influence between the Flipped Classroom-based problem-based learning model and the critical thinking skills of fifth-grade students of UPT SPF SD Inpres Btn Ikip I Makassar City.